Prevalence and factors associated to child abuse in communities from the Colombian Atlantic and Pacific Coasts (2006)
Informationa Plan has been working with communities fromthe Colombian coasts and has found that child abuse is one of their main problems. Objectives: To determine the prevalence of child abuse and its different formsin six communities of the Colombian Atlantic and Pacific Coasts. To identify factors associated to child abuse in those communities and their relative weight. To take the first step in the development of a future intervention program. Methodology: Multi-method study. 1. Identification existing data recollection. 2. Qualitative: focus groupswith parents and teachers, and role games with children to know the studied populations perspective on the topic. 3. Quantitative cross sectional study. 1800 families from the area were randomly selected to answer a questionnaire. Results: Prevalence; Child abuse 67.7%, physical abuse 52.4%, emotional abuse; 27.6%, abandonment; 17.1%, neglect; 10.1% and sexual abuse 1.24%. Child abuse, physical abuse, abandonment and neglect were higher in the Pacific Coast. Emotional and sexual abuse were higher in the Atlantic Coast. These differences are statistically significant. The fictors with stronger associations are: low family income p=0.086, high number of people livingin the house p less than 0.001 and specially minderage p less than 0.01, respondent without couple p=0.022,no public utilities p less than 0.001, bad educational services p=0.032, intergenerational transmission p less than 0.001, partner violence p less than 0.001, external violence p=0.012, living in the pacific region p=0.017, school violence p less than 0.001, believes (naughty children) p=0.072, no activities parents children p=0.019. The factors are different depending on the area. Discussion: Chile abuse is an epidemic problem in the studied area and requires intervention. Severe cases are a priority in well as the control of factors with the highest associations.